Lifestyle Mediates Financial Attitudes and Self-Concept in Student Consumption: Gaya Hidup Memediasi Sikap Keuangan dan Konsep Diri dalam Konsumsi Mahasiswa - Sherly Anindhya Meyra Love Tiananta; Muhadjir Anwar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Urban living has influenced student lifestyles, often fostering consumptive behaviors. Specific Background: Overseas students are particularly vulnerable, facing peer pressure and environmental shifts that affect their financial decisions and self-perception. Knowledge Gap: Existing studies report inconsistent findings regarding how financial attitudes and self-concept affect consumption behavior, particularly lacking the mediating role of lifestyle. Aims: This study investigates whether lifestyle mediates the relationship between financial attitudes, self-concept, and the consumption behavior of overseas students. Results: Using a quantitative approach with SmartPLS 4 and data from 114 FEB UPN Veteran East Java students, the study found that both financial attitudes and self-concept negatively relate to lifestyle and consumption behavior, while lifestyle has a positive relationship with consumption and serves as a mediator. Novelty: The study provides novel insights by integrating lifestyle as a mediating variable, clarifying the previously inconsistent relationships among variables. Implications: The findings suggest that fostering a modest lifestyle may reduce consumptive behavior, even among students with weaker financial attitudes or lower self-concept, guiding effective interventions in student financial education and lifestyle management.Highlight : Lifestyle significantly moderates the link between financial attitude and consumptive behavior. Negative self-concept does not always lead to high consumption due to financial constraints. Students with high allowances and trendy environments are more prone to consumptive lifestyles. Keywords : Lifestyle, Financial Attitude, Self-Concept, Consumptive Behavior, Overseas Students